Are charitable gifts truly appreciated by the recipients who requested them? Impact of gift type and amount on recipients’ appreciation - Kang, In-Hye; Kim, Hyoseok (Journal of Business Research, 2025)
• For requested gifts during rite-of-passage occasions, appreciation for charitable vs. recipient-benefiting gifts depends on gift amount. • For low gift amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. • For moderate to high gift amounts, appreciation is similar between charitable and recipient-benefiting gifts. • In distant (vs. close) giver-recipient relationships, the effect of gift type on appreciation for low amounts is attenuated. • When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts. Requests for charitable cash gifts during rite-of-passage occasions (e.g., weddings) are becoming increasingly common. This research examines whether recipients’ appreciation differs depending on whether a requested cash gift is charitable (e.g., donating to support people in need) or recipient-benefiting (e.g., renovating the recipient’s kitchen). Across five studies, we find that the effect of the gift type on appreciation is moderated by the gift amount. For low amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. However, for moderate and high amounts, appreciation is similar across gift types. This effect is mediated by the recipients’ perception of whether the gift amount meets their expectations and their subsequent perception of thoughtfulness. Consistent with our mechanism, in distant giver-recipient relationships, the effect of the gift type on appreciation for low amounts is attenuated. When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts.
Keywords: Advertising; Business; Charitable gifts; Charitable giving; Conflict of interest; Donation; Economic growth; Economics; Finance; Gift appreciation; Gift giving; Gift price; Gift-giving; Marketing; Psychology; Social psychology; dept.mrk; peer-reviewed

The impact of generative AI on syllabus design and learning - Kim, Hyoseok; Koo, Thomas K. B. (Journal of Marketing Education, 2024)
This research examines the impact of generative artificial intelligence (AI) on the perception of educational content quality, specifically by comparing AI-generated and human-generated course syllabi in marketing education. Results from four studies indicate a general preference for AI-generated syllabi, attributed to their greater perceived objectivity. This preference is more pronounced in conventional courses but diminishes in unconventional ones, suggesting that the unique aspects of these courses may reduce the advantages of generative AI. In addition, disclosing the AI authorship of syllabi significantly affects their perceived quality negatively, underscoring the impact of transparency on the acceptance of AI-generated educational materials. These findings highlight the potential of generative AI in educational content creation and its limitations in certain contexts. They offer valuable insights for enhancing educational practices and shaping policy decisions to enrich student experiences in the era of AI integration.
Keywords: dept.mrk; peer-reviewed